Effect of SCM combinations on paste rheology and its relationship to particle characteristics of the mixture. (1st October 2016) - Shanahan, Natallia; Tran, Victor; Williams, Andrew; Zayed, A.
Highlights: Rheology of ternary OPC/SCM combinations cannot be predicted from binary mixes. Linear relationship between τ0 and BET SSA for pastes with chemical admixtures. Linear relationship between τ0 and packing density for binary OPC/SCM mixes. No significant change in water demand with increasing fly ash and slag content. Water demand increased with increasing silica fume and metakaolin amount. Abstract: Rheological properties of binary, ternary and quaternary combinations of ordinary Portland cement with Class F fly ash, slag, silica fume and metakaolin were evaluated with and without chemical admixtures. A linear relationship was observed between yield stress and BET specific surface area in the presence of chemical admixtures at a constant dosage for binary, ternary and quaternary combination of SCMs. Only binary combinations were examined without chemical admixtures where a linear relationship was observed between yield stress and packing density determined from normal consistency measurements. Although it is typically assumed that the effect of mineral admixtures on rheology is additive, it was observed in this study that combining SCMs did not have an additive effect on apparent yield stress and plastic viscosity, and consequently, these parameters for ternary and quaternary combinations cannot be estimated from their respective values for binary mixtures.